Encapsulation of bioactive whey peptides in soy lecithin-derived nanoliposomes: Influence of peptide molecular weight. (15th December 2016) - Mohan, Aishwarya; McClements, David Julian; Udenigwe, Chibuike C.
Highlights: Encapsulation efficiencies of whey peptide fractions within liposomes were over 90%. Peptide molecular weight did not affect encapsulation efficiency or liposome size. Electrical charge of the liposome was affected by the peptide molecular weights. Peptide size also influenced their distribution in the different regions of the liposomes. The findings are important in designing nanoliposomes for bioactive peptide delivery. Abstract: Encapsulation of peptides can be used to enhance their stability, delivery and bioavailability. This study focused on the effect of the molecular weight range of whey peptides on their encapsulation within soy lecithin-derived nanoliposomes. Peptide molecular weight did not have a major impact on encapsulation efficiency or liposome size. However, it influenced peptide distribution amongst the surface, core, and bilayer regions of the liposomes, as determined by electrical charge (ζ-potential) and FTIR analysis. The liposome ζ-potential depended on peptide molecular weight, suggesting that the peptide charged groups were in different locations relative to the liposome surfaces. FTIR analysis indicated that the least hydrophobic peptide fractions interacted more strongly with choline on the liposome surfaces. The results suggested that the peptides were unequally distributed within the liposomes, even at the same encapsulation efficiency. These findings are important for designing delivery systems for commercial production of encapsulated peptides with improved functional attributes.